CARTOONSAS A MEANSOF INCREASINGTHE MOTIVATIONOF ELEMENTARY STUDENTSIN ENGLISH CLASSROOM - Дементьева, А.В. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
The article discusses the use of video materials in English lessons in elementary school in order to increase the motivation and interest of students, the influence of cartoons on the process of memorizing new language constructions, as well as their influence on the development of oral speech and creative abilities of elementary school students is studied. The author considers the possibilities of creating a free atmosphere in the classroom to encourage students to speak freely and discuss what they have watched.
Keywords: English language; elementary school; video; cartoon; motivation; technology